Efficacy of interval-based training on conditioning of amateur field hockey players - Chapman, D. W.; Newton, M. J.; McGuigan, M. R. (The Journal of Strength and Conditioning Research, 2009)
This research aimed to critically examine the effectiveness of a time-limited and distance-regulated interval training program on subelite field hockey players. Subjects comprised 22 women (26.1 ± 4.5 years, 62.8 ± 7.4 kg, 1.7 ± 0.9 m) and 22 men (22.1 ± 3.2 years, 74.9 ± 5.4 kg, 1.8 ± 0.5 m) field hockey players. Performance tests included a standard 20-m multiple-stage shuttle run (MSSR), a 1000-m repeated-effort (×3) time trial (RTT), and a 100-m repeated-effort (×3) shuttle run (RSR) in an ascending pyramid order. The training program was administered separately to the women and men after a traditional, single-peak, 4-week mesocycle, with the fourth week for recovery. Training consisted of an average total sprint distance of 3000 m per session during a 20-week data collection period, with testing administered pre and post. Initial athlete profiling showed a significant (p < 0.05) gender difference on all performance tests. The MSSR results were 8.6 ± 2.5 (range 6.7-10.7) and 12.1 ± 2.4 (10.2-13.5) women and men, respectively. The RTT and RSR times for women and men were 5:34 ± 0:30 seconds (4:31-6:21), 5:14 ± 0:30 seconds (4:27-6:02), 4:12 ± 0:13 seconds (3:50-4:36), and 4:06 ± 0:13 seconds (3:47-6:02), respectively. After 20 weeks of training, a small to moderate effect size (ES) was calculated for the women's (n = 12) MSSR (ES = 0.74) and RSR (ES = 0.50) results. A distinct improvement in the MSSR resulted after training for men (n = 16), with a moderate ES (1.34). In contrast, completion times in RSR were marginally reduced, with a small ES (0.49). The findings demonstrate that a 3000-m interval-based conditioning program, when conducted in conjunction with normal-skill game play training, can lead to significant improvements in player conditioning during a competitive season. Future research should employ modified performance tests that more accurately reflect the nature of the game.